(untitled) (Bangladesh Journal of Nutrition, 2020)
Drumstick (Moringa oleifera) leaves, locally known as Sajna, have enormous nutritional and medicinal benefits. The study was carried out to formulate drumstick-based functional teas with the aimed to explore alternative uses of Sajna leaves by incorporating with other natural ingredients ginger (Zingiber officinale), holy basil (Ocimum sanctum), lemon grass (Cymbopogon schoenanthus) and stevia (Stevia rebaudiana) leaves. Proximate analysis of all the formulated herbal teas was carried out and the sensory qualities were evaluated by the eleven member taste panels. We used a nine-point hedonic scale for sample’s appearance, texture, flavor, smoothness, smell, color, aesthetic appeal and comprehensive parameters of taste. This study found higher amount of nutrient contents in dried drumstick leaves than the fresh one. In acceptability test regarding the appearance, it was seen that sample-3 was liked very much (>8) by the panel members. It also showed that sample-3 tea (Blended with all other ingredients including lemongrass and stevia) obtained the highest score (8.17 ± 0.55) on the color. On the other hand, in the acceptability test of smell and flavor, it was observed that sample- 3 was liked moderately whereas sample 1 was not liked or disliked by the judges. In acceptability test of smoothness and texture, it was seen from the Hedonic scale points that sample-3 was liked very much (8.57) and moderately liked (>7) by the judges respectively. Based on sensory evaluation, it was concluded that drumstick-based functional tea was acceptable for further consumption, distribution and marketing. Bangladesh J. Nutr. Vol. 33, December 2020, P: 65-72